KEBIJAKAN PENGEMBANGAN PANGAN LOKAL MELALUI PENYULUHAN PERTANIAN MENUJU KEDAULATAN PANGAN DI KABUPATEN BANTUL (DEVELOPMENT POLICY ON LOCAL FOOD THROUGH AGRICULTURAL EXTENSION TOWARD FOOD SOVEREIGNTY IN BANTUL REGENCY) - Wastutiningsih, Sri Peni; Untari, Dyah Woro; Rahmawati, Tri Dyah; Sulistyo, Agus (Jurnal Ilmu-Ilmu Pertanian, 2012)
The objectives of this study are: (1) to know farmer's, agriculture extension officer's, and policy makers' (the stakeholders) comprehension on local food policy, (2) to know the difference of local food policy level among the stakeholders, and 3) to know cooperation pattern between the stakeholders for the implementation of local food policy. The research method used the qualitative data analysis for the first and third objectives, while One Way Anova used to analyze the third objective. The result of the study showed that 1) the stakeholders' comprehension on local food policy was low, socialization through radio, television and print media were needed. 2) There was no significant difference on the local food policy among the stakeholders. 3) The coopera-tion pattern among the stakeholders were well implemented. The development on local food is expected to be more socialized and be able to improve the society welfare.